Nexus between tourism earnings and economic growth: a study of Malaysia - Nanthakumar, Loganathan; Ronald Ravinesh, Kumar; Arvind, Patel (Kluwer Academic Publishers, 2015)
Prior studies on Malaysia mainly looked at the cointegration relationship and causality nexus of the tourism sector. In addition to these apects, in this article, we look at the statistical and economic significance of tourism in Malaysia. We explore the short-run and long-run effects of tourism on output per worker in Malaysia using the sample period 1975–2012 where we estimate the respective elasticity coefficients. Given that the data on tourism receipts reported by the World Bank (2013) are only for 1995–2011 at the time of study, we use an exponential trend function based on the available data for tourism receipts as best fit to approximate the missing data. Subsequently, using the data from 1975–2012 and the augmented Solow (1956) model in which tourism receipts (% GDP) is included as a shift variable and hence a proxy for tourism development, we examine the cointegration, elasticity coefficients and causation using the ARDL bounds (Pesaran et al. 2001) and the Toda and Yamamoto (1995) non Granger causality procedure, respectively. The results show that tourism has a lagged marginal negative effect ( − 0.06 %) in the short run and a positive and statistically significant effect in the long-run (+0.26 %). The causality nexus show a bi-directional causation between tourism and capital per worker which supports the notion that tourism and investment activities are mutually reinforcing; and a unidirectional causation from output per worker to capital per worker indicating that economic growth spurs capital accumulation and productivity. Although our findings are not unique due to data constraints, the results nevertheless reveal that tourism has a long-run momentous effect on the economic growth of Malaysia and is a catalyst for boosting investment activities. In this regard, policy focus can be directed towards enhancing tourism infrastructure including technology integration and management, creating more visitor confidence in the global tourism markets, exploiting the major sources of tourism markets with socially desirable and economically beneficial tourist products, and exploring niche markets for tourism expansion which can include links with foreign direct investment.